Virtual Learning as A Determinant of Students Academic Performance in University of Ilorin During COVID-19 Pandemic - Babalola, Ebenezer Omolafe; Adeyoola, Iyanuoluwa Adewumi; Omolafe, Eyiyemi Veronica (MO.RI Publishing, 2023)
This study examined the influence of Virtual Learning on the Academic Performance of students in University of Ilorin during COVID-19 pandemic. Descriptive research of the survey type was employed for the study. Random sampling techniques was used to select 200 undergraduates who formed the sample size for the study. The study revealed that: Google Classroom is the most utilized virtual learning platform in the sampled schools during COVID-19 pandemic, virtual learning positively influences students’ academic performance during COVID-19 pandemic, students faced challenges while using virtual learning platform for learning during COVID-19 pandemic, there was no significant difference between virtual learning and student’s academic performance during COVID-19 pandemic based on area of specialization and there was no significant difference between virtual learning and student’s academic performance during COVID-19 pandemic based on gender. The study concluded that virtual learning was broadly accepted during COVID-19 pandemic. It is recommended that universities should embrace and utilize more of virtual learning platforms.